2022
DOI: 10.1021/acsanm.1c02665
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fields and Magnetically Stimulated Gold-Coated Superparamagnetic Iron Oxide Nanoparticles Differentially Modulate L-Type Voltage-Gated Calcium Channel Activity in Midbrain Neurons

Abstract: Nanoparticles (NPs) generate localized magnetic forces during magnetic stimulation, which can, in turn, modulate neuronal excitability and regulate downstream signaling in neurons. In agreement with this idea, under static magnetic field stimulation (SMS), gold-coated superparamagnetic iron oxide (Au-SPIO) core–shell nanoparticles (NPs) can promote and guide the direction of neurite outgrowth. Inspired by these promising results, this study investigates how SMS on Au-SPIO (SMS-Au-SPIO) affects the physiology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This enhancement by MF is due to the magnetization of SPIO-Au NPs and the generation of an attractive force, which enhances the translocation of SPIO-Au NPs through the cellular membrane. Our recent work also revealed that the static MF can enhance the uptake of negatively charged SPIO-Au NPs into midbrain dopaminergic neurons, as shown in Figure 3b [18]. A theoretical model was developed by Li et al to study how MFs and magnetic NPs affect the cellular-endocytosis process [50].…”
Section: Toxicity and Cellular Uptake Of Magneto-plasmonic Npsmentioning
confidence: 82%
See 1 more Smart Citation
“…This enhancement by MF is due to the magnetization of SPIO-Au NPs and the generation of an attractive force, which enhances the translocation of SPIO-Au NPs through the cellular membrane. Our recent work also revealed that the static MF can enhance the uptake of negatively charged SPIO-Au NPs into midbrain dopaminergic neurons, as shown in Figure 3b [18]. A theoretical model was developed by Li et al to study how MFs and magnetic NPs affect the cellular-endocytosis process [50].…”
Section: Toxicity and Cellular Uptake Of Magneto-plasmonic Npsmentioning
confidence: 82%
“…Recently, we have shown that SPIO-Au core-shell NPs functionalized with nerve growth factor (NGF) can promote in vitro neuronal growth and differentiation under the stimulation of light [16] and dynamic MF [17]. We have further proven that SPIO-Au NPs in combination with static MF stimulation are capable of regulating calcium fluxes by modulating L-type voltage-gated ion-channel activities, which, in turn, influences the downstream apoptosis signaling pathway in primary midbrain neurons [18]. Noticeably, during this process, the existence of an MF enhances the cellular uptake of SPIO-Au NPs.…”
Section: Superparamagnetic Iron Oxide-gold (Spio-au) Npsmentioning
confidence: 95%
“…We have previously shown that neurons in primary mouse midbrain cultures demonstrate robust spontaneous Ca 2+ fluxes that are strongly inhibited by the L‐type VGCC inhibitor, diltiazem, however, these prior studies did not differentiate between TH + and TH − neurons (Bancroft & Srinivasan, 2020; Yuan et al, 2022). Therefore, we first conducted a series of experiments to specifically characterize spontaneous Ca 2+ fluxes in TH + and TH − neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Since VGKCs are known to play a central role in regulating the frequency of action potentials in neurons (Iyer et al, 2017; Koyama & Appel, 2006; Liss et al, 2001; Martel et al, 2011; Noh et al, 2019), we first assessed the effect of extracellular S100B on VGKC currents in TH + DA neurons. As described previously (Bancroft & Srinivasan, 2020; Srinivasan et al, 2016; Yuan et al, 2022; Zarate et al, 2021), primary mouse ventral midbrain neurons were cultured from ED14 embryos and maintained for ~21 DIV prior to experiments (Figure 2a). Immunostaining of ~3‐week old midbrain cultures showed NeuN + neurons that were either TH + or TH − , along with primary midbrain astrocytes expressing S100B (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Gold has been used as the major coating material on SPION due to its favorable properties such as its low reactivity and its ability to protect the core SPION from external oxidation (Sabale et al 2017;Ling et al 2019;Sheel et al 2020). Hence, SPIONs coated with Au are currently being used as potential magnetic resonance imaging contrast agents, for hyperthermia and other biological systems (Montazerabadi et al 2015;León Félix et al 2019;Stein et al 2020;Yuan et al 2022).…”
Section: Introductionmentioning
confidence: 99%